Recast Subspace Pursuit-based Channel Estimation for Hybrid Beamforming NarrowBand Millimeter-Wave Massive MIMO Systems - Oyerinde, Olutayo Oyeyemi (IEEE Vehicular Technology Conference, 2022)
Millimeter wave (mmWave) wireless communication systems with hybrid beamforming require reliable estimation of channel state information to perform optimally. Though the combined high-speed analog-to-digital converters (ADCs) and hybrid precoder/combiner architecture of this system ameliorate the problem of high-power consumption, they make channel estimation to become cumbersome. The paper proposed a channel estimation scheme that is based on a conventional subspace pursuit algorithm. The proposed estimator is named Recast Subspace Pursuit (ReSP)-based channel estimator. Besides taking advantage of the inherent sparsity in the mmWave Massive MIMO channel, the ReSP-based estimator also exploits the a-priori knowledge of channel matrix support-set as side information for the estimation procedure. Simulation results confirm that the proposed ReSP-based channel estimator can exhibit improved performance than some traditional and earlier proposed channel estimation schemes.